Metacognitive Strategies to Improve Critical Thinking and Learner Autonomy in Writing Argumentative Texts in Islamic Boarding Schools - Imam Nur Aziz; Punaji Setyosari; Utami Widiati; Saida Ulfa (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
This study examines the effects of metacognitive strategies on critical thinking skills and learner autonomy in argumentative writing among students in Indonesian Islamic boarding schools (Mambaus Sholihin Gresik, Amanatul Ummah Mojokerto, Al-Amin Prenduan Madura, and Al-Rosyid Bojonegoro). This study uses mixed methods; the research integrated quantitative data from pre-tests and post-tests with qualitative insights from interviews, questionnaires, and observations to evaluate the strategies' effectiveness. Qualitative findings revealed that applying metacognitive strategies in a four-week argumentative writing module involving goal setting, monitoring, and reflection effectively improved students' critical thinking skills, independence, and writing abilities in Indonesian Islamic boarding schools. Quantitative results indicated that metacognitive strategies significantly enhanced students' abilities to construct coherent arguments and manage the writing process independently (F = 1.540, Sig. = 0.014). However, the overall impact on critical thinking skills and learner autonomy was not statistically significant. Theoretically, the findings confirm that metacognitive strategies enhance analytical and evaluation skills, emphasise the need for contextual adjustments, support the role of peer feedback in boosting metacognitive awareness, and underscore the value of integrating local values to enhance student motivation and independence. Future research should explore the long-term effects, involve more boarding schools, and consider contextual factors such as teacher roles and integration into the Islamic boarding school environment.